2023
DOI: 10.3389/fnins.2023.1139086
|View full text |Cite|
|
Sign up to set email alerts
|

Altered cerebral neurovascular coupling in medication-overuse headache: A study combining multi-modal resting-state fMRI with 3D PCASL

Abstract: AimStructural and functional changes in the brain have been identified in individuals with medication-overuse headache (MOH) using MRI. However, it has not been clearly established whether neurovascular dysfunction occurs in MOH, which could be elucidated by examining neurovascular coupling (NVC) from the viewpoints of neuronal activity and cerebral blood flow. The aim of this study was to investigate potential alterations in NVC function of the brain in individuals with MOH using resting-state functional MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…It is important to note that the connection between neuronal activity and CBF is poorly understood. It is worth noting that two studies have reported the likelihood of irregularities in the neurovascular system among individuals who experience chronic migraines (Hu et al., 2019), and in patients with medication‐overuse headaches (Li et al., 2023). A recent study has shown that individuals with migraine (chronic migraine and episodic migraine) have a higher density of veins compared to healthy individuals, and the correlation between gray matter vein density and functional activity observed in healthy individuals was not found in those with migraine (González et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the connection between neuronal activity and CBF is poorly understood. It is worth noting that two studies have reported the likelihood of irregularities in the neurovascular system among individuals who experience chronic migraines (Hu et al., 2019), and in patients with medication‐overuse headaches (Li et al., 2023). A recent study has shown that individuals with migraine (chronic migraine and episodic migraine) have a higher density of veins compared to healthy individuals, and the correlation between gray matter vein density and functional activity observed in healthy individuals was not found in those with migraine (González et al., 2023).…”
Section: Introductionmentioning
confidence: 99%